Four Laws of Consumption1. Issue 310 (18th July 2019) - Clements, Kenneth W.
Abstract : Scientific knowledge can be distilled into a set of laws that are sufficiently general and robust to be useful in describing and predicting behaviour – the behaviour of physical objects (the orbits of the planets, for example), invisible forces (electricity), economies (why some prosper and others languish) and people (education as deliberate investment in human capital). This paper identifies four empirical regularities in consumption behaviour that are sufficiently general and pervasive to qualify as 'laws': Engel's law; the law of demand (the downward‐sloping demand curve); quantities more dispersed than prices; and the 'law' of - 1 2 for price elasticities. In each case, I survey previous research, use international evidence to illustrate the workings of the laws and demonstrate their practical use.